Secure Electoral Platform Enhancing Transparency in E-Voting Processes (International Journal of Information Technology and Computer Engineering, 2025)
The integration of secure and transparent technologies in electoral processes has become essential to uphold democratic values and public trust. E-voting systems, powered by blockchain technology, offer a transformative approach to achieving these goals by ensuring transparency, security, and efficiency. This study explores the design and implementation of a secure electoral platform that leverages blockchain to enhance the transparency and integrity of e-voting processes. By eliminating paper waste and reducing logistical dependencies, the proposed platform supports sustainable practices while fostering greater voter participation. The integration of artificial intelligence (AI) and machine learning (ML) further optimizes the platform by enabling real-time fraud detection, improving voter authentication, and enhancing system performance during peak usage. Employing the Technology Acceptance Model (TAM), this research investigates citizen perceptions of the platform, highlighting the roles of perceived ease of use, trust, and security in driving adoption. The findings reveal that trust in the platform and its perceived security significantly influence voter acceptance, emphasizing the importance of robust and user-friendly designs. This study provides valuable insights for developers and policymakers aiming to implement secure and transparent e-voting systems, paving the way for more accountable and inclusive electoral processes in the digital era.